ASPECTOS TEÓRICO-METODOLÓGICOS DAS DISSERTAÇÕES DA LINHA 1, POLÍTICAS EDUCACIONAIS, HISTÓRIA E ORGANIZAÇÃO DA EDUCAÇÃO, DO PROGRAMA DE PÓS-GRADUAÇÃO EM EDUCAÇÃO DA UNIVERSIDADE ESTADUAL DO CENTRO-OESTE (PPGE/UNICENTRO-PR) - CHIMEL, LUCIANE (2020)
This research may be characterized as a meta-research, considered as Research about researches (MAINARDES, 2018b). Meta-research aims at analyzing theoretical and methodological bases used in a determined text samples. Therefore, the sample was delimited by 56 dissertations from 2014 to 2018, Line 1 - Educational Policies, History and Organization of Education, of the Graduation Program in Education of the State University of Midwest (PPGE/UNICENTRO) as study object in this research. Methodological research path is guided by bibliographical research assumptions based on the authors of the educational policies and meta-research field, such as Krawczyk (2019; 2012), Stremel (2014; 2016), Mainardes (2017; 2018a, 2018b), Tello and Mainardes (2015), Tello and Almeida (2013), Tello (2012); Sánchez Gamboa (2006), Tonieto (2018), Camargo (2018), Carvalho (2019), Morais (2019), among others. Further the bibliographic research, a documental one was also carried out, in which documents issued by PPGE/UNICENTRO were analyzed (Doctor Degree in Education approved project, compulsory subject programs – Research Line 1, Program regulation – Determination no 7 -CEPE/UNICENTRO, March 24th, 2016, and dissertations produced within the Research Line 1 - PPGE/UNICENTRO, from 2014 to 2018). Research field was performed through semi structured interviews with professors; and questionnaires with alumni from the Research Line 1 - PPGE/UNICENTRO from 2014 to 2018. The study was carried out from the concepts of combined theorizing and added theorizing (MCLENNAN, 1996), and Meta Research proposal in educational policy. It was possible to identify the predominance of explicit historical-dialectical materialism in 35 of dissertations in Line 1 (62.5%); the subjects linked to schools, universities and municipal secretariats were the most pointed participants in the empirical investigations, totaling 20 studies (35.71%). It is highlighted that 51 master students (91.04%) from PPGE / UNICENTRO explain the theoretical perspectives used in the dissertations; qualitative research was the methodological approach most used and made explicit by 14 master students (25%). On the coverage of dissertations of Line 1 PPGE/UNICENTRO, most of the works converge specifically for the local scope, with 31 dissertations. Empirical research was the most used by the researchers of the Line 1 in the program, totaling 31 dissertations (55.36%). Semi structured interviews were mentioned in 25 dissertations in the Line 1 (44.64). This study is an attempt to use and improve the concepts of meta research in Educational Policy. Therefore, the sample presents limitations. It is important highlight that the same objects might be classified in different ways, because every classification is arbitrary (MAINARDES, 2018b). The result of this classification occurred according to the statement of the researchers in their research; ergo, the analysis was based on the concept explicated in the categories listed. However, it is detached that the theoretical and methodological assumptions used does not ensure their use by the researcher in the text content.